Brief answers to the big questions - Hawking, Stephen, 1942-2018; Redmayne, Eddie, 1982-; Thorne, Kip S.; Hawking, Lucy (New York : Bantam Books, 2018)
Offers the renowned scientist's final thoughts on using science to address the most important challenges facing humanity.
Why we must ask the big questions -- Is there a god? -- How did it all begin? -- Is there other intelligent life in the universe? -- Can we predict the future? -- What is inside a black hole? -- Is time travel possible? -- Will we survive on Earth? -- Should we colonise space? -- Will artificial intelligence outsmart us? -- How do we shape the future?
Includes index.
Keywords: Science -- Miscellanea